👤

For numbers 5-7: Use the figure below to supply the missing statement and reasons to prove that MA + AT > MH given that MH = MT. M Given: MH = MT Prove: MA + AT > MH STATEMENT REASON 1. MH MT = 2. (6) (5) Triangle Inequality Theorem (7) 3. MA + AT > MH 5. A. Given C. Triangle Inequality Theorem D. Exterior Angle Theorem B. Hinge Theorem 6.A. MA + AT > MT C. MA + AT = MT D. MA + AT S MT B. MA + AT ​

For Numbers 57 Use The Figure Below To Supply The Missing Statement And Reasons To Prove That MA AT Gt MH Given That MH MT M Given MH MT Prove MA AT Gt MH STATE class=